2009
DOI: 10.1038/leu.2009.186
|View full text |Cite
|
Sign up to set email alerts
|

A different ontogenesis for chronic lymphocytic leukemia cases carrying stereotyped antigen receptors: molecular and computational evidence

Abstract: Chronic lymphocytic leukemia (CLL) is uniquely characterized by the existence of subsets of cases with quasi-identical, 'stereotyped' B-cell receptors (BCRs). Herein we investigate this stereotypy in 2662 patients with CLL, the largest series yet, using purpose-built bioinformatics methods based on sequence pattern discovery. Besides improving the identification of 'stereotyped' cases, we demonstrate that CLL actually consists of two different categories, based on the BCR repertoire, with important biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
120
1
26

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(152 citation statements)
references
References 46 publications
5
120
1
26
Order By: Relevance
“…Despite these shared features, the vast majority of IGHV1-2*04 rearrangements did not fulfill the established criteria for VH CDR3 stereotypy, as defined previously in other lymphoid malignancies, namely CLL, 8,28 mainly because of variable IGHJ gene usage and heterogeneous junctional residues.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Despite these shared features, the vast majority of IGHV1-2*04 rearrangements did not fulfill the established criteria for VH CDR3 stereotypy, as defined previously in other lymphoid malignancies, namely CLL, 8,28 mainly because of variable IGHJ gene usage and heterogeneous junctional residues.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, interpretation of results for all cases was performed de novo in the context of this study, following the approaches reported in our recent publications. 8,24,28 Molecular modeling In order to explore the possible modifications in the antibody structure caused by a single amino-acid replacement---namely, the arginine (R)-totryptophan (W) substitution at position VH FR3-75 to obtain an IGHV1-2*04-rearranging antibody---we performed a molecular dynamics study of the human anti-polyhydroxybutyrate antibody F v : IGHV1-2*02 IGKV1-39*01/1D-39*01 (Protein Data Bank code 2D7T). Replacement of the VH FR3-75 R (germline for IGHV1-2*02) by the W residue (germline for IGHV1-2*04) was executed by the COOT algorithm.…”
Section: Pcr Amplification Of Ighv --Ighd --Ighj Rearrangementsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 However, the most compelling immunogenetic piece of evidence is the fact that almost 30% of CLL patients share BcRs with restricted, quasi-identical IG sequences. 3 This might justifiably be taken as a convincing hint of restriction also in terms of the antigens selecting CLL progenitors. Elucidation of the identity of the respective antigens combined with knowledge about the actual structure of CLL BcRs should aid in understanding the functional interplay between CLL cells and the (micro)environment, eventually paving the way to the design of rational, individualized treatment.…”
mentioning
confidence: 99%